Social-political aspects of German periodicals in Russia of the XIX century - K. V. Petrov (Библиосфера)
This article contains an analysis of social-politically oriented German regional press in Russia in the 30-60s of the 19th century. The main purpose of this study is to determine its characteristics and trends discussed in the context of the state censorship reaction. The author establishes the subject scope of periodicals in general and their articles. The issues raised by German authors cover the social-political problems of the Baltic provinces, their relationships with government, foreign political situation, especially in Prussia, etc. This research work is a result of a synthesis of historical facts based on archival documents, including documents of censorial departments, which existed in the 19th century at the Russian Ministry of National Education and the Ministry for Internal Affairs. Through a comprehensive analysis of official documents, the author identifies several criterions, according to which different political periodicals were evaluated by censorship: periodicals main character, content of particular newspapers or magazines, editions structure and presence of political headings in them.